Body Mass Index Status; Underweight In Active TB Patients at H. Andi Sulthan Daeng Radja's Hospital - Andi Tenriola; Ewit Irianti; Muriyati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Tuberculosis (TB) is a serious public health problem causing increasing morbidity and mortality rates and is of global concern. In tuberculosis (TB) sufferers experience poor nutrition which can reduce a person's immune system so that the disease can easily occur, a lack of protein as well as calories and iron can increase the risk of pulmonary tuberculosis. Objective: To determine the body mass index (BMI) of Tuberculosis (TB) sufferers at H. Andi Hospital. Sultan Daeng Radja Bulukumba Method: This research uses a quantitative type of research using a cross-sectional research design. The number of respondents was 99 people, with a sampling technique using total sampling. This research uses univariate analysis to analyze the data. Results: The body mass index of patients suffering from tuberculosis, found 57 (57.6%) respondents who had a low BMI, in the normal category there were 34 (34.3%) respondents, while in the overweight category, there were 8 respondents with a presentation of (8.1 %). Conclusions and Suggestions: The body mass index of patients suffering from tuberculosis is more likely to be underweight. Tuberculosis patients are expected to be more regular in taking medication so that therapy goals can be achieved as well as regulating diet and improving nutritional status which can influence recovery so that it can improve the patient's body mass index. Keywords: BMI; Tuberculosis; Body Mass Index; Underweight; TB